A survey of critical care nurses' practices and perceptions surrounding early intravenous antibiotic initiation during septic shock. (August 2017) - Roberts, Russel J.; Alhammad, Abdullah M.; Crossley, Lindsay; Anketell, Eric; Wood, LeeAnn; Schumaker, Greg; Garpestad, Erik; Devlin, John W.
Abstract: Background: Delays in antibiotic administration after severe sepsis recognition increases mortality. While physician and pharmacy-related barriers to early antibiotic initiation have been well evaluated, those factors that affect the speed by which critical care nurses working in either the emergency department or the intensive care unit setting initiate antibiotic therapy remains poorly characterized. Aim: To evaluate the knowledge, practices and perceptions of critical care nurses regarding antibiotic initiation in patients with newly recognised septic shock. Methods: A validated survey was distributed to 122 critical care nurses at one 320-bed academic institution with a sepsis protocol advocating intravenous(IV) antibiotic initiation within 1 hour of shock recognition. Results: Among 100 (82%) critical care nurses responding, nearly all (98%) knew of the existence of the sepsis protocol. However, many critical care nurses stated they would optimise blood pressure [with either fluid (38%) or both fluid and a vasopressor (23%)] before antibiotic initiation. Communicated barriers to rapid antibiotic initiation included: excessive patient workload (74%), lack of awareness IV antibiotic(s) ordered (57%) or delivered (69%), need for administration of multiple non-antibiotic IV medications (54%) and no IV access (51%). Conclusions: Multiple nurse-related factors influence IV antibiotic(s) initiation speed and should be incorporated into sepsis quality improvement efforts.